“Old sertão of ages”: perceptions about the aging of the sertaneja population in Serra do Cabral, Minas Gerais (PerCursos, 2023)
From research in the rural area of northern Minas Gerais, this essay examines the connection between the territorialization imposed by modernisation in sertão and the aging conditions of its inhabitants, in order to critically analyze the discardability of the old person in the contemporary world. Based on field research, interviews and bibliographic analysis between the reading of Grande sertão: veredas, it discusses how aging takes place in territories marginalized by the capital movement, rescuing by the memory of the interviewees the sertaneja historicity and its sociability as a form of resistance, collapse or adaptation to economic homogenization. As a result, particular ways of existence and perception of the sertão were presented, indulcing the urgency of another treatment to the elderly by integrating them into the debates and projects that envision a more generous society with its elders.
Keywords: sertão; territorialization; modernization; aging; gender